Elite dualism and leadership selection in China - Zang, Xiaowei (RoutledgeCurzon studies on China in transition, 2004)
This book studies the rulers of China - its top political leaders. It seeks to understand who they are, how job assignment in high politics is determined, and how the Chinese leadership is stratified.